Evaluasi Hambatan Safety Management System (SMS) Pada Pengendalian Lalu Lintas Udara di Perum LPPNPI Cabang Yogyakarta - Dinda Sari; Rezty Fauziah Novianty (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Aviation safety is a fundamental aspect of the aviation industry that must be maintained through structured and measurable systems. One strategic approach is the implementation of a Safety Management System (SMS), as mandated by the Indonesian Ministry of Transportation Regulation No. 62 of 2017. This study aims to evaluate the barriers to SMS implementation in air traffic control operations at Perum LPPNPI Yogyakarta Branch. The research was conducted from June 2025, using a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. The evaluation model used is CIPP (Context, Input, Process, Product) to identify challenges in implementation and their impact on operational safety. The findings reveal that major obstacles in SMS implementation include limited personnel understanding of safety culture, inadequate facilities and technological support, and suboptimal incident reporting systems. Additionally, resistance to change and a lack of regular training contribute to the ineffectiveness of SMS application. This study recommends enhancing human resource competencies, strengthening the safety culture, and conducting continuous evaluations to ensure that SMS is not merely an administrative requirement, but is truly integrated into daily operations to improve aviation safety in the Yogyakarta area.